The diversity of edible plants traded in Ir. Soekarno Market, a traditional market in Sukoharjo District, Indonesia - AVYDA KOZA DEANOVA; CELIN MAYLANI PRISTIAWATI; DEWI APRILIA; IVO SOLIKAH; MARHCELINA NURCAHYATI; NOR LIZA; WHIDI HIMAWAN; RUHYAT PARTASASMITA; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Deanova AK, Pristiawati CM, Aprilia D, Solikah I, Nurcahyati M, Liza N, Himawan W, Partasasmita R, Setyawan AD. 2021. The diversity of edible plants traded in Ir. Soekarno Market, a traditional market in Sukoharjo District, Indonesia. Biodiversitas 22: 4095-4105. Market is one of the most important economic sectors in a country. One type of market is a traditional market that is synonymous with squalid, overcrowded and slum conditions. However, traditional markets provide essential commodities that are relatively cheaper and fresher than modern markets. The purpose of this research was to record the diversity of species and varieties of edible plants traded in Ir. Soekarno Market, a traditional market in Sukoharjo District. Plant commodities observed were vegetables, spices, fruits, and staples sold by the sellers in this market. The method used in this research was qualitative based on the ethnobotany approach. Meanwhile, to collect primary data, several field techniques were used, namely direct observation such as market commodity surveys, trader observations, and trader interviews. The direct survey results showed that the edible plant commodities consisted of 105 plant species representing 28 families. The variations found included 9 types of rice, 4 types of onions, 7 types of bananas, and 9 types of beans. The decline in the number of traded commodities and the lack of visitors was due to the increase in COVID-19 cases in Sukoharjo and disputes between traders and local government. Thus until recently, Ir. Soekarno Market, which was originally the main market full of visitors, became a market that was empty of visitors and traders.